Atención farmacéutica en la bibliografía nacional e internacional - María Victoria Rojo Manteca (Fundación Pharmaceutical Care España, 2021)
A mixed method study design to explore the adherence of haematological cancer patients to oral anticancer medication in a multilingual and multicultural outpatient setting: The MADESIO protocol The influence of intervention complexity on barriers and facilitators in the implementation of professional pharmacy services - A systematic review Therapeutic optimization through goal-oriented prescription in nursing homes